6(3n-8)-5(2n+7)=

Simple and best practice solution for 6(3n-8)-5(2n+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(3n-8)-5(2n+7)= equation:


Simplifying
6(3n + -8) + -5(2n + 7) = 0

Reorder the terms:
6(-8 + 3n) + -5(2n + 7) = 0
(-8 * 6 + 3n * 6) + -5(2n + 7) = 0
(-48 + 18n) + -5(2n + 7) = 0

Reorder the terms:
-48 + 18n + -5(7 + 2n) = 0
-48 + 18n + (7 * -5 + 2n * -5) = 0
-48 + 18n + (-35 + -10n) = 0

Reorder the terms:
-48 + -35 + 18n + -10n = 0

Combine like terms: -48 + -35 = -83
-83 + 18n + -10n = 0

Combine like terms: 18n + -10n = 8n
-83 + 8n = 0

Solving
-83 + 8n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '83' to each side of the equation.
-83 + 83 + 8n = 0 + 83

Combine like terms: -83 + 83 = 0
0 + 8n = 0 + 83
8n = 0 + 83

Combine like terms: 0 + 83 = 83
8n = 83

Divide each side by '8'.
n = 10.375

Simplifying
n = 10.375

See similar equations:

| 3r+12/6=4r-4/4 | | X^2-5x=9-3x^2 | | 8x+12-5x-9= | | 8x+2=8(x+4) | | 5/2x=15/12 | | 3x+11-6x=15-14x+11x-4 | | 3(2x+1)-5=6x-2 | | 0.06(y-9)+0.04y=0.08y-0.01(60) | | 1/3+10u=y/v | | 6=-2910n+7 | | 8-(3+7)=23 | | 0.4x+56000(0.2+x)=1400 | | B=xm+m | | 2y^3+2+6y^2+6y= | | 4(3+5x)=47 | | 5p-13=8p+4 | | 5x-3+3(2x+2)=-3(x+3) | | tn=5n+7 | | 7x+8x=13x | | 6x+7-2x=19 | | 5x+7(x-1)=-3 | | 2y-6=2x | | 5a+10=3a+10 | | x+(x*0.07)=35.19 | | 14(t-6)+4t=6(3t+5)-8 | | (6x-6)-(13x+8)= | | 3x-5(x-3)=16-4x | | x+(x*0.07)=28.25 | | -13x=234 | | -(4y+4)-(-3y-8)=-2 | | 1/4+3/8x=3/4 | | 3.5+0.75x=17.00 |

Equations solver categories